ACODE Benchmarks for Technology Enhanced Learning. (Australasian Council on Open Distance and eLearning (ACODE), 2014)
The ACODE benchmarks have been developed to assist institutions in their practice of delivering a quality technology enhanced learning experience for their students and staff (recognising that some institutions refer to their practice with terms such as e-learning, online or flexible learning, blended, etc.). There are eight benchmarks, each of which can be used as a standalone indicator, or used collectively to provide a whole of institution perspective. However, where these benchmarks become even more powerful is when they are used in association with other institutions, as part of a collaborative benchmarking exercise. [Publisher summary, ed]